Subdental synchondrosis and anatomy of the axis in aging: a histomorphometric study on 30 autopsy cases - Gebauer, Matthias (Springer-Verlag, 2005)
During skeletal development the two ossification centers of the odontoid process are separated from the corpus of the axis by a subdental synchondrosis. This synchondrosis is thought to close and disappear spontaneously in adolescence although this has never been studied in detail. The basis of the dens is of clinical relevance as type II dens fractures are located here. To characterize the morphological architecture of the axis with particular attention to the subdental synchondrosis, the complete axis was harvested from thirty age-matched and gender-matched patients of the three different age groups at autopsy. The subdental synchondrosis and the bone structure of the dens, the basis of the dens and the body of C2 were analyzed by radiography, histology and quantitative histomorphometry. At the macroscopic level the persistency of the subdental synchondrosis in the adult cervical spine was detected in 87% (26 of 30) of the specimens. Histomorphometry revealed a residual disc blastema with an average size of 25.8% of the sagittal depth of the basis of the dens at this level. Bony integration of the synchondrosis was poor throughout all ages. Histologically a cartilaginous matrix composition of the subdental synchondrosis persisted throughout all groups. The trabecular microarchitecture demonstrated a significant reduction of bone volume and trabecular number as well as an increased trabecular separation within the basis of the dens as compared to the corpus or the dens of C2. This histomorphometric data regarding a poor integration of the synchondrosis into the trabecular network and the reduced bone mass within the basis of the dens might offer a previously underestimated explanation for the occurrence of type II dens fractures and their association with pseudoarthrosis, respectively.